Optimization of IPAS learning outcomes through the implementation of the Numbered Heads Together (NHT) cooperative learning model - Ahmad Fauzan Hermandi; Subhanadri Subhanadri (Universitas Pendidikan Indonesia, 2025)
The purpose of this research is to improve student learning achievement in Ilmu Pengetahuan Alam dan Sosial (IPAS) subjects through the application of a cooperative learning model of the Numbered Heads Together (NHT) type developed with an Integrated Science approach, in grade V students of SDN 27/II Sungai Arang. This research employs the Penelitian Tindakan Kelas (PTK) method, which is conducted in two cycles. Each cycle comprises the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 14 students, and data collection was carried out through observation, learning outcome evaluation tests, and documentation of the learning process. The results of the analysis revealed an increase in teacher performance in both Cycle I and Cycle II. A similar increase was also seen in student involvement, which was reflected in increased activeness, teamwork, and a sense of responsibility in group activities. According to the academic results, all students achieved scores above the Kriteria Ketuntasan Minimal (KKM) set. The application of the NHT model has proven effective in creating a more interactive, interesting, and meaningful learning process. Referring to the study's results, the NHT model is suggested as an effective alternative learning strategy to improve the quality of science learning in elementary schools, while strengthening students' social and cognitive competence. Abstrak Tujuan penelitian ini adalah untuk meningkatkan prestasi belajar peserta didik pada mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) melalui penerapan model pembelajaran kooperatif tipe Numbered Heads Together (NHT) yang dikembangkan dengan pendekatan Sains Terpadu, pada peserta didik kelas V SDN 27/II Sungai Arang. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, di mana setiap siklus meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian berjumlah 14 peserta didik, pengumpulan data dilakukan melalui observasi, tes evaluasi hasil belajar, serta dokumentasi proses pembelajaran. Hasil analisis mengungkapkan adanya peningkatan kinerja guru pada siklus I dan siklus II. Peningkatan serupa juga terlihat pada keterlibatan peserta didik, yang tercermin dari meningkatnya keaktifan, kemampuan bekerja sama, dan rasa tanggung jawab dalam kegiatan kelompok. Dari hasil akademik, seluruh peserta didik memperoleh nilai di atas Kriteria Ketuntasan Minimal (KKM) yang ditetapkan. Penerapan model NHT terbukti efektif dalam menciptakan proses pembelajaran yang lebih interaktif, menarik, dan bermakna. Mengacu pada hasil penelitian, model NHT disarankan sebagai salah satu strategi pembelajaran alternatif yang efektif untuk meningkatkan kualitas pembelajaran IPA di sekolah dasar, sekaligus memperkuat kompetensi sosial dan kognitif peserta didik. Kata Kunci: hasil belajar; NHT; Numbered Heads Together; pembelajaran kooperatif